Safety and effectiveness of transarterial embolization for splenic artery hemorrhage in patients undergoing radical gastrectomy. (August 2018) - Han, Kichang; Kim, Man-Deuk; Diffley, Michael; Kwon, Joon Ho; Kim, Gyoung Min; Choi, Woosun; Kim, Yong Seek; Lee, Junhyung; Won, Jong Yun; Lee, Do Yun
Background: Perigastric lymph nodes are dissected during gastrectomy, potentially resulting in life-threatening postoperative bleeding. Purpose: To evaluate the safety and effectiveness of transarterial embolization (TAE) for bleeding from the splenic artery in patients who underwent gastrectomy. Material and Methods: Between January 2004 and December 2016, 14, 523 patients underwent gastrectomy at our institution, and ten patients (nine men; mean age = 64.7 years; age range = 51–80 years) underwent TAE for postoperative bleeding from the splenic artery. The location of bleeding was classified as either: (i) the main splenic artery (MSA) or (ii) the parenchymal splenic artery (PSA). The clinical outcomes of TAE were explored. Results: Bleeding occurred at a median of 13.5 days (range = 4–34 days) after gastrectomy. The onset of bleeding was late in all patients and clinically manifested as abdominal bleeding in seven patients and luminal bleeding in three patients. Technical and clinical success rates were 100% and 70%, respectively. The three major complications occurred only in patients with MSA bleeding, resulting in two 30-day mortality cases and one splenic abscess with fistula formation to the jejunum. The causes of death were infarctions in the spleen and/or remnant stomach and sepsis. Conclusion: TAE seems to be effective in stabilizing patients with bleeding from the splenic artery. Moreover, TAE with curative intent may be performed for bleeding from the PSA; however, further resection of the remnant stomach and/or spleen seems to be required to avoid sepsis and mortality in case of bleeding from the MSA.